2021
DOI: 10.1186/s13567-021-00960-8
|View full text |Cite
|
Sign up to set email alerts
|

Cellular and humoral immune responses associated with protection in sheep vaccinated against Teladorsagia circumcincta

Abstract: Due to increased anthelmintic resistance, complementary methods to drugs are necessary to control gastrointestinal nematodes (GIN). Vaccines are an environmentally-friendly and promising option. In a previous study, a Teladorsagia circumcincta recombinant sub-unit vaccine was administered to two sheep breeds with different levels of resistance against GIN. In the susceptible Canaria Sheep (CS) breed, vaccinates harboured smaller worms with fewer eggs in utero than the control group. Here, we extend this work, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 33 publications
1
5
1
Order By: Relevance
“…In contrast to previous experimental GIN infection studies that included older (approximately 6 month-old) animals [16,23], we found no evidence that CHB lambs were more resistant to T. circumcincta than CS lambs at three months of age. However, great individual variability in resistance regarding parasitological parameters was observed within both breeds.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…In contrast to previous experimental GIN infection studies that included older (approximately 6 month-old) animals [16,23], we found no evidence that CHB lambs were more resistant to T. circumcincta than CS lambs at three months of age. However, great individual variability in resistance regarding parasitological parameters was observed within both breeds.…”
Section: Discussioncontrasting
confidence: 99%
“…In conclusion, the lambs that controlled parasitological parameters more efficiently developed protective type-2 immune responses, similar to those developed by adult animals in other studies [23]. Future study designs will confirm the data presented; for example, by creating resistant and susceptible lineages and exploring the dynamics of the immune response with changes in gene expression throughout infection.…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…Proteomic characterization of these EVs and identified several proteins involved in various functions such as structure and metabolism of the parasite. Importantly, it was found that some of these proteins can be bound by two types of antibodies, IgA and IgG, in T. circumcinctainfected sheep suggesting that these proteins may have potential as vaccine targets for the development and production of a vaccine against T. circumcincta infection [27]. Proteomic analysis could identify proteins carried by extracellular vesicles (EVs) released by tapeworms.…”
Section: Helminthsmentioning
confidence: 99%
“…Protective host immune responses against GINs are mediated by type 2 immune responses involving the infiltration of eosinophils, globule leukocytes, and plasma cells in the abomasal tissue and an increase in the production of cytokines and parasite-specific antibodies ( McRae et al., 2015 ). These host immune responses play important roles in regulating the damage caused by these parasites and are associated with lower egg production and excretion by adult worms, lower parasitic burden, and shorter female parasites ( Machín et al., 2021 ).…”
Section: Introductionmentioning
confidence: 99%